Public Reason in the TIme of Covid-19 - Hands, Joss (Javnost-The Public, 2022)
In the long history of democracy some notion of rational intercourse has always played its part. A common arena, whether concrete or abstracted, has provided a capacity for the exchange of opinion, argument and for arbitration and decision making. While the nature of this arena has evolved, a shared understanding of what the grounds of agreement, and disagreement, has usually been evident. This consensus has come under radical question in contemporary politics. The attendant concepts of communicative, or public reason — the former most closely associated with the critical theorist, philosopher and sociologist, Habermas, and the latter with the political philosopher Rawls has also been challenged from left and right. This article will present a defence of the use of public reason as an important component of the fight against COVID-19, and in the cause of both democracy and social solidarity — as these ideals have come under strain in the first decades of the twenty-first Century.